Design of a small patch antenna at 3.5 GHZ for 5g application - Ferdous, N. (2020)
In this paper a low profile patch antenna has been designed for 5G communication application. The resonating frequency has been chosen as 3.5 GHz for 5G application. FR4 epoxy material with permittivity of 4.3 has been chosen for the substrate material which has fire redundant property. The size of the substrate is 25.2×48 mm2. The main radiating patch is in a shape of ellipse and the line feed technique is used. The simulation is done by CST microwave studio software. Different parameters like S-Parameter, Antenna Gain, Directivity, Efficiency has been observed. The antenna has a gain of more than 5 dB which is very useful for communication applications. The antenna is designed for 5G communication applications. © Published under licence by IOP Publishing Ltd.